Illusory Drifting within a Window That Moves across a Flickering Background. (December 2014) - Anstis, Stuart; Kaneko, Sae
When a striped disk moves across a flickering background, the stripes paradoxically seem to move faster than the disk itself. We attribute this new illusion to reverse-phi motion, which slows down the disk rim but does not affect the stripes.